Analysis of Public Service Quality at The Bumi Ayu Lurah Office - Fitra Hadi Khaz; Ernita Puspa Dewi; Rudi Hartasetiadi; Rahmihayati Rahmihayati (International Journal of Humanities and Social Sciences Reviews, 2024)
Public service is a key aspect of government performance that directly affects community satisfaction. This study examines the quality of public service at the Bumi Ayu Subdistrict Office in Dumai Selatan, Dumai City, using five dimensions: reliability, responsiveness, empathy, tangibles, and assurance. Data were collected through observation, interviews with two informants (one official and one service user), and document review. The findings indicate that public services are generally effective. Staff demonstrate adequate reliability and responsiveness, show empathy in serving the community, provide sufficient facilities to support service activities, and foster public trust through professional conduct. Supporting factors include well-organized service procedures, adequate infrastructure, and attentive staff, while limitations involve dependency on the subdistrict head for document approval, limited staff during peak hours, and some facility constraints. The study highlights the need to improve service timeliness, increase staff availability, and improve facilities to optimize public service delivery. Enhancing training programs for staff and implementing technology solutions for document processing could contribute to further improving service quality. Future research could focus on expanding the scope of public service assessments to include citizen satisfaction and feedback, providing insights into the areas requiring attention for continuous improvement.